Knowledge, attitude and practices towards consumption of caffeine containing drinks among the student population of Ras al-Khaimah medical and health sciences university, UAE - Bhojaraja, Vijayalakshmi S.; Janardhan, Harshitha; Hameed, Najila Abdul; A. R., Fahmidha Gulsoom; Ali, Maryam Zulfiqar (International Journal of Research in Medical Sciences, 2017)
Background: Caffeine, world’s most widely consumed and legally accepted psychoactive substance which is commonly found ingredient in many drinks like coffee, tea, carbonated drinks and energy drinks. The objective was to explore how much dependent are the teenagers and young adults on caffeine containing drinks, reasons and circumstances for the consumption and to know the knowledge and attitude of the consumers about the health effects of the caffeine containing drinks. Methods: A validated questionnaire was administered randomly to about 298 students from MBBS, BDS, B Pharma and Nursing programmes of RAK Medical and Health Sciences University (RAKMHSU). Results: Out of 298 students in the study, 97% (n=290) of them drink caffeinated beverages in the form of coffee (53%), tea (43%), energy drinks (17%), carbonated drinks (18%) and all of the above (11%). The major reasons for consuming varied, where more than half of them gave the reason as to keep them awake for study purpose (53%), to get refreshed (51%), taste and flavour (49%). About 56% were of an opinion that they do experience different symptoms if they don’t consume their daily caffeine intake. 54% students admitted their caffeine consumption has been increased after joining the university. When knowledge and attitude were questioned, 63% of them think caffeine addiction is a health issue and majority of them were aware of the ingredients of these drinks but not the safest amount. Conclusions: Drinking caffeine containing drinks by the students are variable from different sources, so monitoring is necessary for the daily intake and there is need for educational programmes about the health effects related to high consumption of caffeine.